Los overruling de la jurisprudencia constitucional - Fernández Segado, Francisco (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2006)
The aim of this paper is to study the guidelines issued by the Spanish Constitutional Court to modify its own doctrine and the jurisprudential problems created due to these changes.